Electroencephalogram as a Validation Method in Usability Testing - Guntur Maulana Zamroni; Dinan Yulianto; Bella Saphira; Fadel N. Akhmad; Fakhira A. Zahrah (JUITA: Jurnal Informatika, 2023)
Usability testing is a recommended main testing method to evaluate the usability or ease of use of a software. However, this approach can induce bias. Usability testing with survey method using questionnaire instruments and interview has a risk of generating lack of objectivity from the participants because the facilitator can influence the evaluation results. The evaluation process is not optimal and the biases that arise from usability testing can affect the success or failure of a software in the market. A method for validating usability testing results needs to be studied to ensure whether the test results obtained are valid and unbiased. Electroencephalogram (EEG) is one of the tool that can be used to validate usability testing. This study aims to conduct usability testing of the three most popular e-marketplace applications in Indonesia. From the results it can be seen that usability testing using user-based testing gives a fairly good result in term of accuracy. Usability testing using EEG gives lower results than user-based testing. Nevertheless, we cannot rule out EEG as a usability testing method in the future.